Évolution du concept de dangerosité en criminologie européenne (« Vingt ans après... ») - Houchon, Guy (Criminologie, 1984)
In this article, we examine how dangerousness is a concept which is now scrutinized in Europe in terms of criminal policy, clinical criminology and criminology in general. On the one hand, new rationales based on the fear of crime shed some light on criminal policy; on the other, the current conceptual crisis in criminology must not lead to a refusal to perceive serious problematic situations which really affect some persons. Social intervention interrogates us in a critical perspective linked to the abolitionist model.